A new subaerial alga, Vischeria hainanensis sp. nov. (Eustigmatophyceae), from Hainan Island, China - Zhu, Weiju; Xing, Zengyu; Lan, Lingrong; Jiang, Xiaodie (Phytotaxa, 2026)
A new subaerial species of Eustigmatophyceae, Vischeria hainanensis, is described based on material collected from Hainan Island, China. This species resembles V. stellata but is distinguished by its smooth cell wall in early culture stages. Morphological characteristics of V. hainanensis are described in detail, and phylogenetic analyses of 18S rRNA and ITS2 sequences place it within a distinct clade, well-separated from other Vischeria species. Both morphological and molecular evidence support the recognition of this alga as a new species, thereby increasing the known diversity of subaerial Eustigmatophyceae in China.